Identification and Characterization of the Vitellogenin Receptor Gene and Its Role in Reproduction in the Alligatorweed Flea Beetle, Agasicles hygrophila - Zhang, Hong; Liu, Yiran; Jin, Jisu; Zhou, Zhongshi; Guo, Jianying (Frontiers in Physiology, 2019)
Agasicles hygrophila is an effective biological control agent for the invasive weed Alternanthera philoxeroides, and because of this it has been introduced to many parts of the world where A. philoxeroides is a problem. Despite this, there are no reports at present about the reproduction of this important insect. Vitellogenin receptors (VgRs) belong to the superfamily of low-density lipoprotein receptors (LDLRs). One of the roles of VgRs is to regulate the absorption of yolk protein in insects. In this study, the full length vitellogenin receptor gene (AhVgR) from A. hygrophila was sequenced and found to encode a predicted protein of 1,642 amino acids. Sequence analysis of AhVgR revealed that it contains conserved structural motifs common to LDLR family members, and a phylogenetic analysis placed AhVgR as a separate group among the order Coleoptera. AhVgR was found to be specifically expressed in ovarian tissues, and it is first transcribed in the newly-emerged females. The expression patterns are consistent with VgR genes in other insects. RNA interference (RNAi)-mediated suppression of AhVgR gene expression in adult A. hygrophila females inhibited yolk protein deposition in the ovaries, shortened the ovariole, drastically reduced egg production, and ultimately led to a decrease in fecundity. In summary, our work shows that AhVgR is critical for transporting Vg into the oocytes and plays an important role in A. hygrophila reproduction.